Testing the knowledge of nurses regarding the prevention of falls - Horová, Jana; Brabcová, Iva; Krocová, Jitka (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2020)
Objectives: The most frequent adverse events in the institutional medical environment are patient falls. The education of medical workers on this issue is an effective preventative intervention. One of the effective methods of education is e-learning. Goal: The goal of this paper is the assessment of the features of knowledge tests of e-learning courses, which are focused on the prevention of patient falls and designed for nurses who work at ward blocks. Methods: Statistical methods were used for the assessment of the features of knowledge tests of e-learning courses for medical workers (Shapiro–Wilk test, Cronbach alpha coefficient). Results: The Cronbach alpha coefficient for the internal task consistency of the entrance test was 0.82 and 0.85 for the final test. The correlation coefficient between the results of the entrance test and the final test was not statistically significant (p = 0.179), but it was statistically significant regarding the total numbers of correct answers in the entrance test and the final test (p = 0.046). The coefficient value was 0.467, which means a weaker direct correlation. The positive dependence between the entrance test and the final test shows good test validity. Conclusions: We found sufficiently strong results in test reliability and confirmed a positive dependence between the entrance test and the final test. We succeeded in compiling knowledge tests whose features are measurable and reproducible.
Keywords: Education; E-learning course; General nurse; Prevention of falls; Reliability; Validity